2006
DOI: 10.1097/01.mao.0000231590.57348.4b
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Evoked Myogenic Potentials in Acute Acoustic Trauma

Abstract: The greater the noise intensity, the severer damage on the cochlea and saccule is shown. Absent or delayed VEMPs in ears after acute acoustic trauma may indicate poor prognosis with respect to hearing improvement, whereas normal VEMP is not a powerful indicator for expectation of hearing improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…The nonsyndromic nature of Cx30 Ϫ/Ϫ mutant mice could be explained by vestibular compensation, which is a well-known phenomenon confirmed in patients after unilateral removal of vestibular schwanoma (Wiegand et al, 1996). This interpretation is consistent with the fact that most Cx mutant patients (Sheykholeslami et al, 2004;Wang et al, 2006). In addition, the Tullio effect, whereby high-level sound stimulation induces eye movements and postural changes, could conceivably be used to test saccule dysfunction further in Cx30 Ϫ/Ϫ mice (Dieterich et al, 1989).…”
Section: Discussionsupporting
confidence: 79%
“…The nonsyndromic nature of Cx30 Ϫ/Ϫ mutant mice could be explained by vestibular compensation, which is a well-known phenomenon confirmed in patients after unilateral removal of vestibular schwanoma (Wiegand et al, 1996). This interpretation is consistent with the fact that most Cx mutant patients (Sheykholeslami et al, 2004;Wang et al, 2006). In addition, the Tullio effect, whereby high-level sound stimulation induces eye movements and postural changes, could conceivably be used to test saccule dysfunction further in Cx30 Ϫ/Ϫ mice (Dieterich et al, 1989).…”
Section: Discussionsupporting
confidence: 79%
“…Recently, the VEMP test has been adopted to evaluate the impact of noise on the saccule, which is anatomically proximal to the footplate of the stapes, and this test has been validated to reflect the sacculo-collic reflex (Uchino et al, 1997). Previous reports by the authors revealed that subjects with acute acoustic trauma or chronic noise-induced hearing loss may display abnormal VEMPs, indicating that the severity of damage to the cochlea and saccule increases with noise intensity (Wang et al, 2006;Wang & Young, 2007). Since the effects on hearing and VEMPs by occupational and recreational noise exposure have been investigated, it should be valuable to study those of gunshot noise exposure.…”
Section: Sumariomentioning
confidence: 98%
“…There is increasing evidence for noise-induced vestibular deficiency, through a mechanism of noise-induced damage to the sacculocolic reflex pathway and/or damage to the vestibular hair cell cilia [62, 130]. This is supported by multiple studies in human and animals.…”
Section: Beyond Hearing Loss: Associated Symptomatologymentioning
confidence: 99%